KEWENANGAN MEMBUAT AKTA PERTANAHAN ANTARA NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH DI KOTAMADYA SINGKAWANG - , Erna Fahriati, Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this research is to answer: (1) authority differences in making the land act between the Notary and The Functionary of Land Act Maker in the Municipality of Singkawang